Music and Dyslexia: A New Musical Training Method to Improve Reading and Related Disorders - Habib, Michel; Lardy, Chloé; Desiles, Tristan; Commeiras, Céline; Chobert, Julie; Besson, Mireille (Frontiers in Psychology, 2016)
Numerous arguments in the recent neuroscientific literature support the use of musical training as a therapeutic tool among the arsenal already available to therapists and educators for treating children with dyslexia. In the present study, we tested the efficacy of a specially-designed Cognitivo-Musical Training (CMT) protocol based upon three principles : 1- music-language analogies : training dyslexics with music could contribute to improve brain circuits which are common to music and language processes; 2 – the temporal and rhythmic features of music, which could exert a positive effect on the multiple dimensions of the “temporal deficit” characteristic of dyslexia; and 3- cross-modal integration, based on converging evidence of impaired connectivity in dyslexia and related disorders. Accordingly, we developed a series of musical exercises involving jointly and simultaneously sensory (visual, auditory, somatosensory) and motor systems, with special emphasis on rhythmic perception and production in addition to intensive training of various features of the musical auditory signal. Two separate studies were carried out, one in which dyslexic children received intensive musical exercises concentrated over 18 hours during three consecutive days, and the other in which the 18 hours of musical training were spread over six weeks. Both studies showed significant improvements in some untrained, linguistic and non-linguistic variables. The first one yielded significant improvement in categorial perception and auditory perception of temporal components of speech. The second study revealed additional improvements in auditory attention, phonological awareness (syllable fusion), reading abilities and repetition of pseudo-words. Importantly, most improvements persisted after an untrained period of 6 weeks. These results provide new additional arguments for using music as part of systematic therapeutic and instructional practice for dyslexic children.